Projeto de oficinas literárias: um olhar para a sala de aula - Grasiela Aparecida Coutinho (2021)
In research are required research related in the field of education, in an attempt to explain the linguistic processes, even more about the teaching / learning process, and this is confirmed when students enter elementary school. Often, the student does not perform the activities simply because he does not want to, but because he does not know, does not understand what to do, as he cannot even read what is asked or because he cannot establish a dialogue with the teacher or a colleague asking for help . Children, even if they cannot read and write as little as necessary, are usually promoted from one year to the next in the name of the promise that one day, alone, they will be able to learn. This perspective ends up discharging the school to seek strategies for these children to learn. Thinking about these unfilled gaps, it is necessary to rethink the teaching practice, adopting differentiated teaching practices so that our students advance and so that there is social interaction both inside and outside the boundaries of the school. In this Literary Workshops Project, a work is proposed which seeks to develop practices that improve teaching practice. The objective is to propose and develop activities aimed at reading and understanding fictional narrative texts, selected according to the target audience and with a view to improving learning, developing reading and writing skills and, consequently, social interaction of students . The implications are fundamentally based on the theories of Soares (2007, 2017), Kleiman (2005, 2007, 2014), Antunes (2003), Compagnon(2009), Cosson (2009), Paiva (2003), Rojo (2009, 2012).